What does an African ethic of social cohesion entail for social distancing?. Issue 1 (8th June 2020) - Metz, Thaddeus
Abstract: The most prominent strand of moral thought in the African philosophical tradition is relational and cohesive, roughly demanding that we enter into community with each other. Familiar is the view that being a real person means sharing a way of life with others, perhaps even in their fate. What does such a communal ethic prescribe for the coronavirus pandemic? Might it forbid one from social distancing, at least away from intimates? Or would it entail that social distancing is wrong to some degree, although morally permissible on balance? Or could it mean that social distancing is not wrong to any degree and could, under certain circumstances, be the right way to commune? In this article, I defend the latter view. I argue that, given an independently attractive understanding of how to value communal relationship, distancing oneself from others when necessary to protect them from serious incapacitation or harm can come at no cost to right action. However, I also discuss cases in which social distancing would evince a lack of good character, despite being the right thing to do.